PENGARUH BUDAYA ISLAM DI PULAU MISOOL, KABUPATEN RAJA AMPAT - Mene, Bau (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
Raja Ampat is part of the province of West Papua which consists of four major islands, namely Pulau Waigeo, Salawati, Batanta and Misool and small islands in the vicinity. Misool Island is located in the southern part of the range of the Raja Ampat archipelago. The area is geographically possible to the cultural contacts with the Islamic community, such as Ternate and Tidore. Research with archaeological survey found some evidence of the influence of Islamic culture in the district of South Misool, West Misool, Misool Misool East and North. The findings in the form of manuscripts, musical instruments, tombs, mosques, the former palace, Klauster settlements, old wells and finding fragments of ceramics and pottery and stone swearing. In addition, at the time the site of Islam, during the later also received the Dutch colonial influence as evidenced by the discovery of a police station, the hostel employee Netherlands, and the Dutch administrative offices. This shows that the dimensions of the site are very diverse and its dynamics will be described in this paper.